2012
DOI: 10.7314/apjcp.2012.13.8.3879
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Women's Interest in Breast Cancer Gene Testing: Possible Influence of Awareness, Perceived Risk and Socio-demographic Factors

Abstract: Background: Development of effective educational strategies should accompany increases in public awareness and the availability of genetic testing for breast cancer (BC). These educational strategies should be designed to fulfill the knowledge gap while considering factors that influence women's interest in order to facilitate decision making. Objective: To determine the possible correlates of Saudi women's interest in BC genes testing including socio-demographics, the level of awareness towards BC genes, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 43 publications
7
26
1
Order By: Relevance
“…Recent study done on awareness of BC warning signs and screening methods among female residents of Pokhara Valley at Nepal by Sathian et al (2014) also supported finding by adding that high SES women are exposed to health-related issues through mass media, internet and a better socioeconomic status enables support of screening services. Similar associations with SES were observed by Kanaga et al in Malaysia (Kanaga et al, 2011) and Amin et al in Saudi Arabia when enquiring about BC gene testing awareness (Amin et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Recent study done on awareness of BC warning signs and screening methods among female residents of Pokhara Valley at Nepal by Sathian et al (2014) also supported finding by adding that high SES women are exposed to health-related issues through mass media, internet and a better socioeconomic status enables support of screening services. Similar associations with SES were observed by Kanaga et al in Malaysia (Kanaga et al, 2011) and Amin et al in Saudi Arabia when enquiring about BC gene testing awareness (Amin et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Inconsistent to our findings, the previous reports stated a higher level of knowledge compared to Saudi population, where only 18.6% and 23.1% correctly picked up the cancer types prevented by PA namely colon and breast cancers respectively. Coups et al (2008) found that only 15% of the included U.S sample knew about the role of PA in colon cancer prevention, a close figure to ours (Coups et al, 2008).Women in this study were more aware about the role of PA in preventing breast cancer this could be explained by the frequent campaigns held in the last several years about breast cancer prevention in the Eastern Province of Saudi Arabia and the higher perceived risk of breast cancer among them (Amin et al, 2012b), Physical Activity and Cancer Prevention: Awareness and Meeting the Recommendations among Adult Saudis.…”
Section: Discussionsupporting
confidence: 72%
“…This study found that exactly half of the patients in a primary care setting wanted to have their genetic risk of salt sensitivity hypertension assessed. This is consistent with the 43–76% rate at which participants in other studies, including cancer patients, the relatives of cancer patients, and attendees of the educational component of a breast cancer awareness campaign, have been interested in genetic testing for cancers and hereditary diseases in previous studies [9,12,13,16,17]. …”
Section: Discussionsupporting
confidence: 86%
“…Studies have also focused on patients attending cancer clinics, [12-14] or receiving direct-to-consumer genetic testing [15]. Two studies performed in primary care settings examined awareness of genetic risk of hereditary diseases [16] and breast cancer [17]. However, the proportion of primary care patients who are willing to undergo genetic testing for common diseases, aside from cancer, remains unknown.…”
Section: Introductionmentioning
confidence: 99%